T helper 2 and T follicular helper cells: Regulation and Function of Interleukin-4 - Sahoo, Anupama (Cytokine Growth Factor Rev, 2016)
Type 2 immunity is characterized by expression of the cytokines interleukin (IL)-4, IL-5, IL-9 and IL-13, which can function in mediating protective immunity in the host or possess a pathogenic role. T helper (Th) 2 cells have emerged to play a beneficial role in mediating anti-parasitic immunity and are also known to be key players in mediating allergic diseases. In addition to the Th2 cells, recent studies have identified T follicular helper (Tfh) cells as an alternative source of IL-4 to regulate type 2 humoral immune responses, indicating that Th2 and Tfh cells exhibit overlapping phenotypical and functional characteristics. Th2 and Tfh cells appear to utilize unique mechanisms for regulation of IL-4 expression; however unlike Th2 cells, the regulation and function of Tfh-derived IL-4 is not yet fully understood. Understanding of the molecular mechanisms for IL-4 expression and function in both cell subsets will lead to development of pharmacological approaches to regulate the function of IL-4 in different disease settings.